THE EFFECTIVENESS OF GROUP COUNSELING SERVICES USING AGGRESSION CONTROL METHODS TO REDUCE THE TENDENCY OF BULLIYING BEHAVIOR IN JUNIOR HIGH SCHOOL STUDENTS - Azharo, Atika; Rusman, Abdul Aziz (Counsenesia Indonesian Journal Of Guidance and Counseling, 2025)
Bullying is an aggressive behavior repeatedly carried out by individuals or groups in physical, verbal, social, or psychological forms. This phenomenon has become a serious concern due to its negative impact on the mental and physical health of victims, particularly within the school environment, which is supposed to be a safe space. This study aims to examine the effectiveness of group counseling services using the Aggression Control Methods technique in reducing students' tendency toward bullying behavior. The research was conducted on 11th-grade students of SMP Swasta Syuhada Sukaraja in the 2024/2025 academic year. This study employed a pre-experimental research method with a one-group pretest-posttest design and a quantitative approach. The sample was selected using purposive sampling, and data were collected through a questionnaire. Data analysis was conducted using non- parametric statistical techniques, specifically the Wilcoxon Signed-Rank Test. The test result showed a significance value of 0.012. Since the Asymp. Sig value of 0.012 < 0.05, the alternative hypothesis (Ha) is accepted. This indicates a significant difference in students’ bullying behavior between the pretest (before the intervention) and the posttest (after the intervention). Therefore, it can be concluded that group counseling using Aggression Control Methods is effective in reducing the tendency of bullying behavior among 11th-grade students at SMP Swasta Syuhada Sukaraja.